Photodynamic Therapy: Promoting In Vitro Efficacy of Photodynamic Therapy by Liposomal Formulations of a Photosensitizing Agent - Rizvi, Imran (Lasers Surg Med, 2018)
OBJECTIVE: A relatively low level of lysosomal photodamage has been shown capable of promoting the efficacy of photodamage simultaneously or subsequently directed to mitochondrial/ER sites. The procedure has hitherto involved the use of two photosensitizing agents that require irradiation at two different wavelengths and different formulation techniques. This, together with different pharmacokinetic profiles of the photosensitizers, adds a layer of complexity to a protocol that we have sought to circumvent. In this study, liposomal formulations were used to direct photodamage created by benzoporphyrin derivative (BPD, Verteporfin) to lysosomes, mitochondria and the ER. This resulted in the development of an optimal targeting profile using a single agent and a single wavelength of activating irradiation. MATERIALS/METHODS: These studies were carried out in monolayer cultures of OVCAR5 tumor cells. BPD localization was modified by lipid anchoring and formulation in liposomes, and was assessed by fluorescence microscopy. Irradiation was carried out at 690±10 nm with photodamage assessed also using fluorescent probes and microscopy. RESULTS: BPD normally localizes in a wide variety of sub-cellular loci that include both mitochondria and the ER, but lysosomes are spared from photodamage. Using a liposomal formulation containing BPD anchored to a lipid resulted in the targeting of lysosomes. A mixture of liposomes containing “free” and “anchored” BPD was shown to significantly promote photokilling. Eliminating cholesterol from the formulation of the anchored product enhanced lysosomal photodamage; prior studies had revealed that excess cholesterol can have a cytoprotective effect when lysosomes are the PDT target. DISCUSSION: The ability of a liposomal formulation to change localization patterns permits directing photodynamic therapy toward specific sub-cellular loci, thereby promoting photokilling. Incorporating chemotherapeutic agents into such formulations could represent a logical next step in assessing the ability of directed photodamage to enhance tumor eradication. Lasers Surg. Med. 50:499–505, 2018. © 2018 Wiley Periodicals, Inc.